Oral care quality-Do humanity aspects matter? Nursing staff's and older people's perceptions - Maria Andersson; Bodil Wilde‐Larsson; Mona Persenius (Wiley, 2020)
Abstract Aim (a) To describe and compare perceptions of humanity aspects of oral care quality in relation to nursing staff in short‐term care units and intensive care units and older people in short‐term care units and their person‐related conditions; and (b) to compare humanity aspects of oral care quality perceptions between nursing staff and older people in short‐term care units. Design Cross‐sectional study. Self‐reported questionnaire and clinical assessments. Methods Nursing staff (N = 417) and older people (N = 74) completed the modified Quality of Care from a Patient Perspective instrument and person‐related items. Older people's oral health status was clinically assessed using the Revised Oral Assessment Guide. Data were analysed using descriptive and analytic statistics. The data were collected from 2013-2016. Results Nursing staff's perceptions of humanity aspects of oral care quality were related to gender, work role and care environment. Older people's perceptions of humanity aspects of oral care quality were related to self‐reported physical health. Nursing staff in short‐term care units perceived the subjective importance of humanity aspects of oral care quality higher compared with older people in short‐term care units.